Answer:
32x-8y-3
Step-by-step explanation:
4(8x-2y)-3
4 x 8x = 32x
4 x 2y = -8y
Figure the fraction of box tops each class collected, then multiply the prize money by that fraction.
Total box tops = 3760 +2301 +1855 = 7916
Mr Coronado's class's fraction: 3760/7916 × $600 = $284.99
Mrs De Souza's class's fraction: 2301/7916 × $600 = $174.41
Mr Nost's class's fraction: 1855/7916 × $600 = $140.60
Answer:
300 seconds
Step-by-step explanation:
The first dog run at v₁ = 15 m/sec the second one run at v₂ = 12 m/sec
we know that d = v*t then t = d/v
Then the first dog will take 300/ 12 = 25 seconds to make a turn
The second will take 300 / 15 = 20 seconds to make a turn
Then the first dog in 12 turns 12*25 will be at the start point, and so will the second one at the turn 15.
To check first dog 12 * 25 = 300
And the second dog 15 * 20 = 300
That means that time required for the two dogs to be at the start point together is
300 seconds, in that time the first dog finished the 12 turns, and the second had ended the 15.
Another procedure to solve this problem is as follows:
between 12 m/sec and 15 m/sec the minimum common multiple is 300 ( 300 is the smaller number that accept 12 and 15 as factors 12*15 = 300) Then when time arrives at 300 seconds the two dogs will be again in the starting point
It could basically be anything smaller than -3. So, some examples are -4,-5-,-6,-7,-8,-9,-10, and so on.
Answer:
![\displaystyle \lim_{x \to -2} \frac{x^3 + 8}{x^4 - 16} = \frac{-3}{8}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%20%5Clim_%7Bx%20%5Cto%20-2%7D%20%5Cfrac%7Bx%5E3%20%2B%208%7D%7Bx%5E4%20-%2016%7D%20%3D%20%5Cfrac%7B-3%7D%7B8%7D)
General Formulas and Concepts:
<u>Calculus</u>
Limits
Limit Rule [Constant]: ![\displaystyle \lim_{x \to c} b = b](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%20c%7D%20b%20%3D%20b)
Limit Rule [Variable Direct Substitution]: ![\displaystyle \lim_{x \to c} x = c](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%20c%7D%20x%20%3D%20c)
Limit Property [Addition/Subtraction]: ![\displaystyle \lim_{x \to c} [f(x) \pm g(x)] = \lim_{x \to c} f(x) \pm \lim_{x \to c} g(x)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%20c%7D%20%5Bf%28x%29%20%5Cpm%20g%28x%29%5D%20%3D%20%20%5Clim_%7Bx%20%5Cto%20c%7D%20f%28x%29%20%5Cpm%20%5Clim_%7Bx%20%5Cto%20c%7D%20g%28x%29)
L'Hopital's Rule
Differentiation
- Derivatives
- Derivative Notation
Derivative Property [Addition/Subtraction]: ![\displaystyle \frac{d}{dx}[f(x) + g(x)] = \frac{d}{dx}[f(x)] + \frac{d}{dx}[g(x)]](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7Bd%7D%7Bdx%7D%5Bf%28x%29%20%2B%20g%28x%29%5D%20%3D%20%5Cfrac%7Bd%7D%7Bdx%7D%5Bf%28x%29%5D%20%2B%20%5Cfrac%7Bd%7D%7Bdx%7D%5Bg%28x%29%5D)
Basic Power Rule:
- f(x) = cxⁿ
- f’(x) = c·nxⁿ⁻¹
Step-by-step explanation:
We are given the following limit:
![\displaystyle \lim_{x \to -2} \frac{x^3 + 8}{x^4 - 16}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%20%5Clim_%7Bx%20%5Cto%20-2%7D%20%5Cfrac%7Bx%5E3%20%2B%208%7D%7Bx%5E4%20-%2016%7D)
Let's substitute in <em>x</em> = -2 using the limit rule:
![\displaystyle \lim_{x \to -2} \frac{x^3 + 8}{x^4 - 16} = \frac{(-2)^3 + 8}{(-2)^4 - 16}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%20%5Clim_%7Bx%20%5Cto%20-2%7D%20%5Cfrac%7Bx%5E3%20%2B%208%7D%7Bx%5E4%20-%2016%7D%20%3D%20%5Cfrac%7B%28-2%29%5E3%20%2B%208%7D%7B%28-2%29%5E4%20-%2016%7D)
Evaluating this, we arrive at an indeterminate form:
![\displaystyle \lim_{x \to -2} \frac{x^3 + 8}{x^4 - 16} = \frac{0}{0}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%20%5Clim_%7Bx%20%5Cto%20-2%7D%20%5Cfrac%7Bx%5E3%20%2B%208%7D%7Bx%5E4%20-%2016%7D%20%3D%20%5Cfrac%7B0%7D%7B0%7D)
Since we have an indeterminate form, let's use L'Hopital's Rule. Differentiate both the numerator and denominator respectively:
![\displaystyle \lim_{x \to -2} \frac{x^3 + 8}{x^4 - 16} = \lim_{x \to -2} \frac{3x^2}{4x^3}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%20-2%7D%20%5Cfrac%7Bx%5E3%20%2B%208%7D%7Bx%5E4%20-%2016%7D%20%3D%20%5Clim_%7Bx%20%5Cto%20-2%7D%20%5Cfrac%7B3x%5E2%7D%7B4x%5E3%7D)
Substitute in <em>x</em> = -2 using the limit rule:
![\displaystyle \lim_{x \to -2} \frac{3x^2}{4x^3} = \frac{3(-2)^2}{4(-2)^3}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%20-2%7D%20%5Cfrac%7B3x%5E2%7D%7B4x%5E3%7D%20%3D%20%5Cfrac%7B3%28-2%29%5E2%7D%7B4%28-2%29%5E3%7D)
Evaluating this, we get:
![\displaystyle \lim_{x \to -2} \frac{3x^2}{4x^3} = \frac{-3}{8}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%20-2%7D%20%5Cfrac%7B3x%5E2%7D%7B4x%5E3%7D%20%3D%20%5Cfrac%7B-3%7D%7B8%7D)
And we have our answer.
Topic: AP Calculus AB/BC (Calculus I/I + II)
Unit: Limits